Aplikasi Mobile Money Management Dengan Fitur Optical Character Recognition Menggunakan Framework React Native - Susana Lin; Genrawan Hoendarto (LP3M Universitas Mulia, 2021)
Financial management is one of the important things in the process of achieving the financial goals of a person or an organization. Everyone has their own way to manages finances, this is dependent on the character and they goals. Financial management can be done conventionally, for example by manual method which is commonly done by write the expenses, income, and savings in a notebook. However, if the note must contain details of the transactions carried out, it can be considered less efficient. The use of Optical Character Recognition will be able to answer this problem, by taking a picture of the transaction, all transaction details will be recorded on the smartphone, and the user can validate the results obtained and save the record on the smartphone user. Users can also immediately see the total transactions made according to the selected time range without having to calculate each transaction made manually. The application will be designed using the react native framework which allows it to run on various platforms.